2013
DOI: 10.1016/j.ceca.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of store-operated Ca2+ channels in pancreatic duct epithelia

Abstract: Store-operated Ca2+ channels (SOCs) are activated by depletion of intracellular Ca2+ stores following agonist-mediated Ca2+ release. Previously we demonstrated that Ca2+ influx through SOCs elicits exocytosis efficiently in pancreatic duct epithelial cells (PDEC). Here we describe the biophysical, pharmacological, and molecular properties of the duct epithelial SOCs using Ca2+ imaging, whole-cell patch-clamp, and molecular biology. In PDEC, agonists of purinergic, muscarinic, and adrenergic receptors coupled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
9
1
1
Order By: Relevance
“…This result was not expected based on our previous finding that activated SOC are localized in the basolateral membrane (Kim et al. ). We interpreted that overexpression of Orai1 proteins, typically 10–100 times more than endogenous proteins, results in mislocalization of the protein to the apical side.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…This result was not expected based on our previous finding that activated SOC are localized in the basolateral membrane (Kim et al. ). We interpreted that overexpression of Orai1 proteins, typically 10–100 times more than endogenous proteins, results in mislocalization of the protein to the apical side.…”
Section: Resultscontrasting
confidence: 89%
“…This location is consistent with basolateral endogenous SOC puncta visualized with an Orai3‐specific antibody (Kim et al. ). By contrast, in the monolayers with Orai1‐STIM1 overexpression, both apical and basolateral Ca 2+ raised intracellular Ca 2+ levels, implicating that apically localized exogenous Orai1 forms functional SOC at the apical membrane, along with basolateral endogenous SOC proteins (Fig.…”
Section: Resultssupporting
confidence: 86%
“…However, it has been found that SOC-mediated Ca 2+ influx can be a driving force for exocytosis, evoked by trypsin (Kim et al, 2008) in dog PDEC. The same authors have shown the function of SOCs in dog PDEC where the typical inward rectifying current was found, as for other types of epithelial cells (Kim et al, 2013). Furthermore, it was found that STIM1, STIM2, ORAI1, ORAI2, and ORAI3 as well as TRPC1 and TRPV6 are all expressed in dog PDEC, where ORAI3 was shown to be the dominant expressing type (Kim et al, 2013).…”
Section: Calcium Channelsmentioning
confidence: 79%
“…These data suggest that TRPC channels are involved in the SOC entry of pancreatic acini cells and could contribute to fluid secretion. Other TRP channels have been found to be expressed in exocrine pancreas; TRPV6 (Kim et al, 2013), TRPM7 (Yee et al, 2011) and TRPM8 (Yee et al, 2010). However, only the role of TRPM7 is described.…”
Section: Calcium Channelsmentioning
confidence: 99%
“…4F). SKF 96365 (100 μM), a compound that blocks both SOCs and DAG-activated TRPC channels [66,69] reducing the Ca 2+ influx across the plasma membrane [70], either completely blocked (Fig. 4G, black trace) or strongly decreased the oscillation frequency.…”
Section: Pharmacological Identification Of Ca 2+ Influx Components Anmentioning
confidence: 98%